2013
DOI: 10.1111/cup.12189
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of virtual microscopy and glass slide microscopy among dermatology residents during a simulated in‐training examination

Abstract: Diagnostic accuracy with virtual microscopy is dependent on year of residency training and prior experience with virtual microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…[4][5][6] Implementation barriers include the cost-benefit of digital pathology, current lack of regulatory approval from the US Food and Drug Administration, a paucity of evidence validating the diagnostic concordance of WSI and light microscopy, and low acceptability of digital pathology among pathologists. 1,[7][8][9][10][11] If digital pathology is to be implemented for primary diagnosis on a large scale, regulatory bodies, both international and national; departmental heads; and individual pathologists will have to be confident that a diagnosis made on a digital microscope is equivalent to a diagnosis made by the same pathologist on a light microscope.…”
mentioning
confidence: 99%
“…[4][5][6] Implementation barriers include the cost-benefit of digital pathology, current lack of regulatory approval from the US Food and Drug Administration, a paucity of evidence validating the diagnostic concordance of WSI and light microscopy, and low acceptability of digital pathology among pathologists. 1,[7][8][9][10][11] If digital pathology is to be implemented for primary diagnosis on a large scale, regulatory bodies, both international and national; departmental heads; and individual pathologists will have to be confident that a diagnosis made on a digital microscope is equivalent to a diagnosis made by the same pathologist on a light microscope.…”
mentioning
confidence: 99%
“…Variation may also depend on level of experience and familiarity with DS. One study found that accuracy with virtual microscopy is dependent on year of residency training and prior experience with virtual microscopy . Further study may be necessary to understand what degree resolution and other facets of digitization including user familiarity of the digitized slides impact the identification of histopathologic features.…”
Section: Discussionmentioning
confidence: 99%
“…Several initiatives, such as the European Association of Pathology Chairs and Residency Program Directors, aim to homogenize the knowledge of residents all over Europe evaluating them by performing a test containing virtual slides [17]. WSI is well evaluated by residents in the studies, although the final results comparing abilities reached with WSI and CLM differ from one study to another [43,44,45]. The presence of clinical and radiological information and previous practice using WSI seem to influence the results [36].…”
Section: Wsi In Postgraduate Training (Residency and Fellowship Progrmentioning
confidence: 99%